PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS TRI HITA KARANA SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN KONSEP - Ketut Bali Sastrawan (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
The Contextual Teaching and Learning (CTL) approach based on one of the local wisdomof the Balinese community, Tri Hita Karana, which is a way of presenting learning materials byexposing students to problems that must be solved or resolved in order to achieve educationalgoals associated with daily life. The base of Tri Hita Karana in applying the CTL model is veryrelevant to the understanding of the meaning of Tri Hita Karana itself. If it is harmonized betweenTri Hita Karana it is very closely related because it is equally concerned with the learningenvironment stakeholders. The contextual Teaching and Learning model is learning that helpsteachers associate material taught with real world situations and encourages students to makeconnections between their knowledge and their application in their lives as family members andsociety. In the learning process understanding the concept of prerequisites for achieving cognitiveabilities or skills at a higher level, both in the same context and in different contexts. Understandingthe concept refers to the ability to determine the express meaning of the material and completemastery of the characteristics, nature and development of concepts.